A new fossil snipe fly with long proboscis from the Middle Jurassic of Inner Mongolia, China (Diptera: Rhagionidae) - Han, Ye; Cai, Yajing; Ren, Dong; Wang, Yongjie (Zootaxa, 2019)
A new genus and species of rhagionids with a long proboscis, Elliprhagio macrosiphonius gen. et sp. nov., is described from the Middle Jurassic Jiulongshan Formation in Daohugou, Inner Mongolia, China, which is considered to be the earliest hematophagous rhagionid described hitherto according to the typically piercing and sucking mouthparts. All previously documented rhagionids from northeastern China are reviewed a key to genera of Rhagionidae from Daohugou is provided for the first time. The genus Daohugorhagio Zhang, 2013 is considered as a new synonym of Trichorhagio Zhang, 2013.